To be continued... comparing the effects of laundry soap sequel commercials with conventional commercials - Potot, Vinalyn Marasigan 1979-
This study seeks to compare the effects of laundry soap sequel commercials with conventional commercials on selected urban-based Filipino wives. Towards this end, the study sets forth the following specific objectives: (a.) To find out if the appeal of laundry soap sequel and conventional commercials are based on the following: Filipino values, plot/story line, actors/actress of commercial, product, respondents' socio-demographic characteristics, and environment of respondents; (b.) To find out the span of attention and involvement or motor responses that the respondents give to laundry soap sequel and conventional commercials respectively; and (c.) To find out which type of laundry soap commercials (sequel or conventional) induces higher retention among selected urban Filipino wives and if high retention translates into sales. The main theory that guides this study is Bandura's Social Learning Theory which states that people learn from direct experience as well as from observation or modeling. Television commercials are specific examples of forms that model events or products. This research uses a quantitative-qualitative method to generate data. These methods include qualitative content analysis, focus interviews and survey. The study reveals that the sequel laundry soap commercial which is Surf has a great impact on the selected urban-based Filipino wives than the conventional ones. Surf surfaces as the most remembered and most familiar advertisement. Although the commercial does not make use of famous and established personalities, the talent recall is evident. The consumers also associate some Filipino values like thriftiness, respect for others, love for fellowmen and obedience to parents in the commercial. Furthermore, wives involved themselves in Surf by watching the commercial from start to finish. Compared with the conventional advertisements, according to the respondents, the commercial has a most interesting and effective story. The ultimate manifestation of this is they purchase Surf rather that the other brands as shown in the results of the survey. Given the choice, the respondents would still prefer sequel commercials versus the conventional ones. However, for a more intensive study it is suggested that two different environments or settings be included to see if environmental factors affects responses of respondents. It is also necessary that interviews be conducted with "sari-sari" store and supermarket owners to supplement the results of the study. The proposal considered the above method but due to limited time the researcher was not able to do so. A sample focus interview guide for the particular respondents is found in the appendices of this research. Also, a more analytical scheme than what this study adopted is also required for future researches. Albert Bandura's Social Learning Theory may be quite traditional for this fast changing world because it specifically says he concrete steps that a person undergoes in making his or her preference for a certain event. It fails to consider that a person is a complex being and the other possible factors may come out during, before or after coming up with their response to particular stimuli.